Diversity of soil Arthropods in Red Chili (Capsicum annuum L.) farm in Sindumartani Village, Ngemplak, Sleman, Yogyakarta - Ichsan Luqmana Indra Putra; Andika Setyo Budi (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2021)
The purpose of this study was to identify soil arthropods and calculate the index of diversity, richness, evenness, dominance and importance index in chili farming land, Sindumartani Village, Ngemplak, Sleman, DIY. The research was conducted by monitoring the research location, sampling and data analysis. The method used is to use a pitfall trap. Data collection was carried out at 3 locations by placing sampling plots at 4 pitfall traps 40 m longEach research location was named station 1, station 2 and station 3. Then the data were analyzed using the formula for diversity index, wealth, evenness, dominance and important value index. The results showed that the soil arthropods found were 8 orders, 11 families and 15 species. The calculation results obtained from the diversity index value (H`) at station 1 is 1.10986, at station 2 is 1.09405 and at station 3 is 1.17118. The value of the species richness index is obtained from data at station 1 which is 1.40877, at station 2 is 1.99049 and at station 3 is 1.79858. The value of the species evenness index obtained by data at station 1 is 0.48201, at station 2 is 0.45208 and at station 3 is 0.50864. The dominance index value obtained by data at station 1 is 0.51820, station 2 is 0.56397 and at station 3 is 0.50471.©2021 JNSMR UIN Walisongo. All rights reserved.